Factors that Influence the Satisfaction of Health Service Recipients in Hospitals: Systematic Literature Review - Astuti, Eka Rati (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
One of the challenges in hospital health services is patient dissatisfaction. Patient satisfaction relates to their feelings about the health services received compared to their expectations. Improving the quality of hospital services is crucial for enhancing patient satisfaction.This study aims to find out the factors that can influence the satisfaction of health service recipients in hospitals. The literature review method was used for journals related to client satisfaction factors and health services in hospitals limited to the years 2019-2024. This research method includes 7 international journals, 4 international journals indexed by Scopus, and 5 national journals, 4 journals certified by Sinta (S3:1 S4: 3). Based on the results of the review, it was found that satisfaction with health services in hospitals was influenced by the following factors: physical evidence (2 journals), reliability (2 journals), responsiveness (2 journals), health insurance (2 journals), empathy (2 journals), religion (1 journal), respondent satisfaction (1 journal), assessment of health services (1 journal), health services (1 journal), limiting the number of patients (1 journal), and standard prevention (1 journal). In conclusion, factors that influence the satisfaction of health service recipients in hospitals include physicality, reliability, responsiveness, health insurance, and empathy.